Efeito da ingestão de diferentes fontes e concentrações de lipídeos sobre parâmetros metabólicos de ratos Wistar obesos - Gondim, Paula Novato (2016)
Obesity is a public health issue that has reached epidemic proportions. It is a chronic disease characterized by the excessive accumulation of body fat. Among its comorbidities are cardiovascular diseases, diabetes mellitus and dyslipidemia. In this sense, this study evaluated the effect of the consumption of different sources and inserted concentrations of lipids in the diet over metabolic parameters of Wistar rats, previously obesity-induced by high-fat diet. The experimental design was completely randomized in a 3x2 factorial arrangement with six replicates per treatment. A total of 36 Wistar rats were fed high-fat diet containing 20% of lard for 12 weeks, in order to cause metabolic obesity. After this period, the animals were divided into six groups, and fed diets with lipid concentrations of 5% or 20% of lard (BA), soybean oil (OS) or fish oil (OP), for 4 weeks. The data were submitted to analysis of variance (two way) followed by post hoc Tukey test (p<0.05). The groups that consumed OP, regardless of the concentration, showed less weight gain and lower serum levels of triacylglycerol (TAG), total cholesterol and fractions (HDL -c, LDL-c+VLDL-c), aspartate aminotransferase (AST) activity, atherogenic index, concentration of fat in the carcass, Lee index and total leukocyte (p<0.05). The same parameters presented higher values in the group that consumed BA (p<0.05). Only in the concentration of 20% OP (p<0.05) did serum glucose, alanine aminotransferase (ALT) and gamma glutamyl transferase (GGT) activities decrease when compared to the other groups with the same fat content (20%). T he groups that consumed OS showed similar values to the OP group regarding weight gain, and reduced values when compared to the BA group (p<0.05). However, total levels of cholesterol and lipoproteins, atherogenic index, concentration of fat in the carcass, Lee index and total leukocyte count were similar in the groups that consumed BA (increased in relation to the OP group). For the remaining parameters, the OS group had intermediate results regarding the other two treatments. With the results obtained, we concluded that the diet intake of fish oil was able to positively modulate metabolic changes resulting from the highfat diet containing 20%fat.